Living With Dementia in Correctional Settings: A Case Report. Issue 3 (July 2018) - Peacock, Shelley; Hodson, Alexandra; MacRae, Rhoda; Peternelj-Taylor, Cindy
Abstract : ABSTRACT: The prison population is aging at an alarming rate and many older persons have the potential to develop dementia while in prison. This case report aims to explore the needs of older people living with dementia in prison and discusses the interventions that exist to address these needs. As the condition progresses, persons with dementia become increasingly reliant on the support of others for their health and well-being because of the increasing complexity of physical healthcare and psychosocial needs. Very few interventions are cited in the research literature regarding the use, acceptability, and/or effectiveness of programming for people living with dementia in prison. To support the unique and complex needs of these persons, research is needed to guide the development of evidence-informed dementia programs and services as well as consideration of interdisciplinary collaboration with community organizations.